Azithromycin effects on the European sea bass (Dicentrarchus labrax) early life stages following acute and chronic exposure: Laboratory bioassays. (4th May 2022) - Mhadhbi, Lazhar; El Ayari, Tahani; Tir, Meriam; Kadri, Dorra
Abstract: The purpose of this study was to assess the acute and chronic effects of the macrolide azithromycin (AZI) on the European sea bass ( Dicentrarchus labrax ) early life stages. Azithromycin is a semi-synthetic antibiotic frequently detected in the aquatic environment, despite this few information about its effects on aquatic organisms were reported. Investigations of AZI acute toxicity on D. labrax early life stages were made using six increasing concentrations (0.625, 1.25, 2.5, 5, 10 and 20 mg/l) during 96 h of exposure. The chronic toxicity was tested at one year old juveniles using two sublethal concentrations (C1 = 0.05 µg/l and C2 = 0.8 µg/l) during 4 and 14 days. Malondialdehyde (MDA), glutathione S-transferase (GST), catalase (CAT) and acetylcholinesterase (AChE) activities were measured in gill and liver tissues of juveniles. The half lethal concentration (LC50 ), 96 h value of AZI for the European sea bass was determined as 31 mg/l. Results showed that short-time exposure to 20 mg/l of azithromycin induces 18% and 7.5% of larvae mortality and morphological abnormalities, respectively. Azithromycin provoked oxidative stress, peroxidative damage, and neurotoxicity in juveniles D. labrax . Overall, the CAT and AChE activities decreased in gill and liver tissues, while dissimilarity in response in both organs depending on AZI concentrations and time of exposure was observed in MDA and GST levels.